A Novel and Efficient Tandem Aldol Condensation–Diels–Alder Reaction Pathway for the Direct Synthesis of Dehydrodecaline Derivatives - Abaee, M. Saeed; Mojtahedi, Mohammad M.; Saberi, Farveh; Karimi, Ghazal; Rezaei, M. Taghi; Mesbah, A. Wahid; Harms, Klaus; Massa, Werner (Synlett, 2012)
An efficient direct synthesis of dehydrodecaline derivatives is reported via a tandem aldol condensation–Diels–Alder cycloaddition process under Lewis acidic conditions. Addition of dienophile moieties to conjugated dienes, formed in situ from the condensation of enone 1 with aldehydes, lead to high-yield stereoselective synthesis of the final endo products in relatively short time periods. Products precipitate upon concentration of the organic phase and are purified by recrystallization.
Keywords: tandem reaction; aldol condensation; Diels–Alder reaction; endo addition; Lewis acid catalysis